2014
DOI: 10.5539/ass.v10n10p86
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Global Financial Crisis on Stock Market Volatility: Evidence from India

Abstract: This paper studies the global financial crisis and the effect of the crisis on stock market volatility by employing the GJR GARCH model. To demonstrate the influence of crisis on stock returns volatility, a dummy variable was introduced in the GJR GARCH model. It is found that the volatility of mean returns had increased during the post crisis period as compared to the pre-crisis period. The findings also suggest that the recent financial crisis had an adverse impact on mean returns and the volatility in the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…In spite the evidence that external finance is necessary to augment domestic saving to accelerate investment (Asiedu, 2002), the global financial crisis in 2008 has led to a substantial decline in import, export and foreign investment inflow to Africa with a consequential loss in market capitalization. Ali and Afzal (2012) affirm that the net capital inflow from advanced to the Bamanga Umar, Sabri Nayan emerging nations declines significantly from the beginning of the crises. Although the crisis was originated in the United States, it spreads to almost all nations with varying degree of damages.…”
Section: Introductionmentioning
confidence: 85%
“…In spite the evidence that external finance is necessary to augment domestic saving to accelerate investment (Asiedu, 2002), the global financial crisis in 2008 has led to a substantial decline in import, export and foreign investment inflow to Africa with a consequential loss in market capitalization. Ali and Afzal (2012) affirm that the net capital inflow from advanced to the Bamanga Umar, Sabri Nayan emerging nations declines significantly from the beginning of the crises. Although the crisis was originated in the United States, it spreads to almost all nations with varying degree of damages.…”
Section: Introductionmentioning
confidence: 85%
“…To measure volatility, they used EGARCH model and found that it had a stronger response to negative shocks. Considering the effect of the same crisis, Sakthivel et al (2014) reported similar findings for the Indian market alone. Amit & Bammi (2016) investigated the volatility of the Indian stock market before, during, and after the 2008-2009 global crisis.…”
Section: Introductionmentioning
confidence: 60%
“…The US based sub-prime lending crisis spread across the world causing global financial crisis. Impact of this crisis was witnessed in Indian securities markets at close of financial year 2007-08, which continued during early 2008-09 (Sakthivel, Veera Kumar, Raghuram, Govindarajan & Vijay Anand, 2014). Therefore, sub-sample period is divided into two parts; before and after Global financial crisis.…”
Section: Data Description and Research Methodologymentioning
confidence: 99%